2009
DOI: 10.1080/00958970802272282
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and luminescent properties of zinc(II) and Hg(II) complexes with substituted 1,10-phenanthroline

Abstract: Two d 10 group 12 metal complexes, 2-(2-methoxyphenyl)-1,10-phenanthroline zinc dichloride (2a) and 2-(2-methoxyphenyl)-1,10-phenanthroline mercury dichloride (2b) were synthesized and characterized by IR, 1 H and 13 C NMR as well as elemental analysis. Structure of 2b in the solid state was determined by single-crystal X-ray crystallography, revealing that 2b is four-coordinate in a distorted tetrahedral geometry with the methoxy group uncoordinated. Luminescent properties of 2a and 2b in solution and the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A number of structures of Pb 2þ and Hg 2þ complexes have been published in the past few years [36][37][38][39][40][41][42][43][44]. For example, Marandi et al [36][37][38] reported a series of Pb 2þ Symmetry transformations used to generate equivalent atoms: #6: Àx, Ày þ 1, Àz; #7: Àx À 1/2, y þ 1/2, Àz þ 1/2; #8: x, y þ 1, z; #9: Àx À 1/2, y À 1/2, Àz þ 1/2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of structures of Pb 2þ and Hg 2þ complexes have been published in the past few years [36][37][38][39][40][41][42][43][44]. For example, Marandi et al [36][37][38] reported a series of Pb 2þ Symmetry transformations used to generate equivalent atoms: #6: Àx, Ày þ 1, Àz; #7: Àx À 1/2, y þ 1/2, Àz þ 1/2; #8: x, y þ 1, z; #9: Àx À 1/2, y À 1/2, Àz þ 1/2.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al [39] synthesized Hg 2þ complexes with substituted 1,10-phenanthroline and studied its luminescent properties. Similar to these ligands, cucurbit [5]uril can coordinate to Pb 2þ and Hg 2þ .…”
Section: Anion Channel 1375mentioning
confidence: 99%